Application of an inverse cascade analytical and numerical design method used in the design of axial fans - Bleiziffer, Mihai; Epple, Philipp; Smith, Henrik; Semel, Matthias; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
This contribution presents an inverse design method for axial flow fans validated by 3-D RANS numerical simulations. It is based on an analytical performance derivation for different free-vortex distributions combined with a mean-line pre-design tool and supported by a new 2-D cascade potential flow computational method. This computes the 2-D planar cascade flow field and the inviscid deflection angle of thin arbitrary shape airfoils at different machine radii followed by a numerical radial integration into a quasi-3-D method. For validation, several fan designs were investigated, showing the influence of important design parameters as well as the potential of the present method by redrafting an industrial fan. The 2-D planar potential cascade code was validated against the Weinig's coefficient diagram for flat plate and circular arc cascades. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.applic